IMMEDIATE LIFTING EFFECT AFTER MICROFOCUSED ULTRASOUND APPLICATION - de Lucca Trombini, Aline; Januzzi Santos, Marcelo (Health and Society, 2023)
High-Intensity Focused Ultrasound (HIFU) treatment is an innovative technique for non-invasive facial aesthetic treatments. This work aims to present the theoretical foundations, mechanism of action, and effectiveness of this technology in facial rejuvenation through a case report. HIFU is a technique based on the emission of focused ultrasonic waves, which act directly on the layers of the skin, stimulating the natural process of collagen and elastin production known as neocollagenesis and neoelastogenesis. By precisely directing ultrasonic energy, it generates heat above 55°C at the focal point, leading to points of thermal coagulation (TCPs) in the target tissue and promoting tissue contraction, resulting in a non-surgical and long-lasting lifting effect. Several scientific studies demonstrating the efficacy of high-intensity focused ultrasound in treating expression lines, skin sagging, wrinkles, and improving facial contour have been reviewed. Furthermore, the technology has been successfully applied in specific areas, such as the periocular region, for treating periorbital wrinkles. The findings indicate that HIFU is safe and well-tolerated by patients, with minimal side effects and associated risks. The absence of recovery time and the possibility of immediate return to daily activities have contributed to the growing popularity of the procedure. In conclusion, high-intensity focused ultrasound emerges as a promising and effective alternative in the field of orofacial harmonization, providing consistent results and patient satisfaction.